STUDY OF WATER QUALITY AT WEST SUNTER RESERVOIR, NORTH JAKARTA BASED ON PHYSICAL AND CHEMICAL PARAMETERS - Muthia Fitriana Hakim; Bambang Iswato; Muhammad Lindu (Universitas Trisakti, 2017)
Aim: This study is to determine effect of contamination level of population settlement activity on water quality in the reservoir at west Sunter by measurements of reservoir water quality in the form of physical and chemical parameters including the identification of the kinetics of COD. Methodology and Result: This research was conducted in April to August 2016 with 11 sampling locations. Research indicated that the reservoir had experienced heavy pollution with DO value ranging between 1.05 mg/L-1.52 mg/L with a minimum quality standard of 3 mg/L, Ammonia 0.13 mg/L-0.38 mg/L with a quality standard of 0.02 mg/L, surfactant (1.74 mg/L-4.63 mg/L) quality standard of 0.2 mg/L and phosphate (0.8 mg/L-1:19 mg/L) to the quality standard of 1 mg/L. Reservoir also were polluted with heavy loads inclusion of organic content with COD values ranging between 112.58 mg/L - 196.39 mg/L. The source of pollution in the west Sunter reservoir was derived from domestic sewage. Based on the average constant value it takes 16.96 hours to reduce the COD from 120 mg/L to 40 mg/L. Natural Retention time at West Sunter Reservoir is 13.6 days. Conclusion, significance and impact study: Domestic waste has obviously contaminated West Sunter reservoir from its physically green color, high organic content with high COD values, low DO, high oil and fat content, and high phosphate levels. These polluted compounds must be removed before spreading to the next water body. If the reservoir is considered as a reactor site, then the reservoir must be able to remove the contaminants before disposal.